Basic structural motif and major biophysical properties of Amyloid-beta are encoded in the fragment 18-35 - Chandrakesan, Muralidharan; Sarkar, Bidyut; Mithu, Venus Singh; Rajiv M. Abhyankar; Bhowmik, Debanjan; Nag, Suman; Sahoo, Bankanidhi; Shah, Riddhi; Gurav, Sushma; Banerjee, Raja; Dandekar, Sucheta; Jose, Jaya C.; et al. (Chemical Physics, 2013)
Aggregation and misfolding of the amyloid beta (A beta) peptide is thought to initiate Alzheimer's disease (AD). Here we study the role played by its central segment (A beta(18-35)) in determining these properties. A beta(18-35) has a solubility of 18 mu M. The soluble fraction consists mainly of small oligomers, which have mixed beta-sheet and random coil structures. The monomer is mostly a random coil with some residual compactness. Aggregated A beta(18-35) forms fibrils of width 3.0 +/- 0.7 nm, which is consistent with a hairpin shape. Each of these properties has a close similarity to A beta(40). Remarkably, solid state NMR indicates that the fibrils also retain the secondary structure and tertiary contacts of A beta(40). This is the shortest fragment of A beta reported so far which preserves its fibrillar architecture, including the hairpin turn, as well as its solution phase conformational properties. Residues 18-35 should therefore be a key target of AD therapeutics. (C) 2013 Published by Elsevier B. V.
Keywords: Alzheimer's disease; Fluorescence correlation spectroscopy; Protein aggregation; Solid-state NMR

Critical roles of key domains in complete adsorption of a beta peptide on single-walled carbon nanotubes: insights with point mutations and MD simulations - Jana, Asis K.; Jose, Jaya C.; Sengupta, Neelanjana (Physical Chemistry Chemical Physics, 2013)
Owing to the influence of nanomaterials on biomacromolecular behavior, their potential applications are rapidly gaining attention. Based on atomistic molecular dynamics simulation studies we have recently reported that the full-length A beta peptide, whose self-assembly is associated with Alzheimer's disease, adsorbs rapidly on single-walled carbon nanotubes, thereby losing its natural propensity to collapse. Here, we investigate the mechanistic overlap between the peptide's compactification and its adsorption, while decoupling the roles of hydrophobicity and aromaticity via point mutations. The collapse mechanism is correlated with interactions between the central hydrophobic core (HP1) and the peptide's C-terminal domain, which are almost exactly compensated by interactions arising from the nanotube after complete adsorption. Adsorption is initiated by HP1 and consolidated by strong interactions arising from the N-terminal domain. Altering the hydrophobicity, but not the aromatic character, of the central residue in HP1 decreases the collapse probability. On the other hand, the adsorption propensity is dramatically reduced when either the hydrophobicity or the aromatic character in HP1 is compromised. The hydrophobicity of HP1 is responsible for dewetting transitions that facilitate its initial interactions with the nanotube, which then lead to very favorable interactions with the nanotube.

Molecular dynamics simulation studies of the structural response of an isolated A beta(1-42) monomer localized in the vicinity of the hydrophilic TiO2 surface - Jose, Jaya C.; Sengupta, Neelanjana (European Biophysics Journal, 2013)
We have probed the effect of a model hydrophilic surface, rutile TiO2, on the full-length amyloid beta (A beta(1-42)) monomer using molecular dynamics simulations. The rutile surface brings about sharp changes in the peptide's intrinsic behavior in a distance-dependent manner. The intrinsic collapse of the peptide is disrupted, while the beta-sheet propensity is sharply enhanced with increased proximity to the surface. The results may have implications for A beta self-assembly and fibrillogenesis on hydrophilic surfaces and should be taken into consideration in the design of novel nanomaterials for perturbing amyloidogenic behavior.
Keywords: Amyloid beta; beta-Sheet propensity; molecular dynamics simulation; TiO2 rutile surface

Cross dimerization of amyloid-beta and alpha synuclein proteins in aqueous environment: a molecular dynamics simulations study - Jose, Jaya C.; Chatterjee, Prathit; Sengupta, Neelanjana (Plos One, 2014)
Self-assembly of the intrinsically unstructured proteins, amyloid beta (A beta) and alpha synclein (alpha Syn), are associated with Alzheimer's Disease, and Parkinson's and Lewy Body Diseases, respectively. Importantly, pathological overlaps between these neurodegenerative diseases, and the possibilities of interactions between A beta and alpha Syn in biological milieu emerge from several recent clinical reports and in vitro studies. Nevertheless, there are very few molecular level studies that have probed the nature of spontaneous interactions between these two sequentially dissimilar proteins and key characteristics of the resulting cross complexes. In this study, we have used atomistic molecular dynamics simulations to probe the possibility of cross dimerization between alpha Syn(1-95) and A beta(1-42), and thereby gain insights into their plausible early assembly pathways in aqueous environment. Our analyses indicate a strong probability of association between the two sequences, with inter-protein attractive electrostatic interactions playing dominant roles. Principal component analysis revealed significant heterogeneity in the strength and nature of the associations in the key interaction modes. In most, the interactions of repeating Lys residues, mainly in the imperfect repeats `KTKEGV' present in alpha Syn(1-95) were found to be essential for cross interactions and formation of inter-protein salt bridges. Additionally, a hydrophobicity driven interaction mode devoid of salt bridges, where the non-amyloid component (NAC) region of alpha Syn(1-95) came in contact with the hydrophobic core of A beta(1-42) was observed. The existence of such hetero complexes, and therefore hetero assembly pathways may lead to polymorphic aggregates with variations in pathological attributes. Our results provide a perspective on development of therapeutic strategies for preventing pathogenic interactions between these proteins.

Microscopic hydration properties of the a beta(1-42) peptide monomer and the globular protein ubiquitin: a comparative molecular dynamics study - Jose, Jaya C.; Khatua, Prabir; Bansal, Nupur; Sengupta, Neelanjana; Bandyopadhyay, Sanjoy (Journal of Physical Chemistry B, 2014)
Atomistic molecular dynamics simulations of eight selected conformations of a disordered protein amyloid beta (1-42) (A beta), and a globular protein, ubiquitin(UBQ), have been carried out in aqueous media at 310 K. Detailed analyses were carried out to compare the microscopic properties of water molecules present in the hydration layers of these systems. It is notices that irrespective of the conformational heterogeneity among the A beta monomers, water molecules hydrating UBQ. Importantly, the conformational heterogeneity of the A beta monomers has been found to affect the translational and rotational motions of hydration water molecules in a nonuniform manner. Detailed investigation of the timescale of hydrogen bond relaxations at the surface and their energetics revealed the possibility of heterogeneous confinement around different A beta conformations. The distribution of water density fluctuation around A beta conformations are broader compared density fluctuation among the A beta monomers suggests that the structural propensities could affect the peptides effective surface hydrophobicity.

Conformational features of the Aβ42 peptide monomer and its interaction with the surrounding solvent - Khatua, Prabir; Jose, Jaya C.; Sengupta, Neelanjana; Bandyopadhyay, Sanjoy (Physical Chemistry Chemical Physics, 2016)